REVIEW OF COMPUTATIONAL FLUID DYNAMIC (CFD) OF SAVONIUS ROTOR FOR TURBINE RENEWABLE ENERGY - Habibie, Alwan; Wahyudi, Hadi; Suprayogi, Dedy Triawan (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2023)
This research aims to establish the accuracy foundation of Computational Fluid Dynamics (CFD) in simulating the utilization of Savonius Rotor in marine currents, particularly in the vast potential waters of Indonesia. The methodology involved a comprehensive review of journal articles, evaluating studies on the application of CFD in simulating the performance of Savonius turbines in marine current environments. The journal review findings indicate the effective use of CFD in replicating Savonius Rotor behavior, particularly in Indonesia's marine current context. The evaluation of CFD simulation accuracy in this study reveals reliable and accurate results, aligning well with experimental data. These findings suggest that CFD is a dependable tool for effectively simulating Savonius Rotor performance in Indonesian marine current conditions, providing a strong foundation for further research on harnessing marine current potential as a renewable energy source in Indonesia.